2020
DOI: 10.1088/2515-7620/ab7ff3
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying forest growth uncertainty on carbon payback times in a simple biomass carbon model

Abstract: In 2018 Sterman et al (2018a) published a simple dynamic lifecycle analysis (DLCA) model for forest-sourced bioenergy. The model has been widely cited since its publication, including widespread reporting of the model's headline results within the media. In adapting a successful replication of the Sterman et al (2018a) model with open-source software, we identified a number of changes to input parameters which improved the fit of the model's forest site growth function with its training data. These relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The carbon payback time depends on how an analysis is temporally framed and other variables, ranging from the alternative fates for the feedstock to the type and location of sourcing forests [79,80]. If, as many models assume, a forest plot is clear-cut for only bioenergy purposes, the carbon payback time for a typical managed pine plantation in the SE US is calculated to be about 18 years, while mixed pine-hardwood, naturally regenerating forest stands may require three times longer [81,82]. However, forests in the SE US are primarily harvested for higher-value markets.…”
Section: Strengths and Weaknesses Of The Se Us Pellet Supply Chainmentioning
confidence: 99%
“…The carbon payback time depends on how an analysis is temporally framed and other variables, ranging from the alternative fates for the feedstock to the type and location of sourcing forests [79,80]. If, as many models assume, a forest plot is clear-cut for only bioenergy purposes, the carbon payback time for a typical managed pine plantation in the SE US is calculated to be about 18 years, while mixed pine-hardwood, naturally regenerating forest stands may require three times longer [81,82]. However, forests in the SE US are primarily harvested for higher-value markets.…”
Section: Strengths and Weaknesses Of The Se Us Pellet Supply Chainmentioning
confidence: 99%
“…34 Recent work suggested that even relative to coal (most institutions are displacing less carbon-intensive natural gas), carbon payback periods for northeastern forests were likely to range from 50 to 100 years. 35 Significantly, even if the ''carbon debts'' are short, front loading of emissions to be offset by later sequestration (i.e., net carbon neutrality over time) still may not be climate neutral. System lags mean that the early pulse of CO 2 will increase the heat trapped in the climate system for years after the pulse has been offset by sequestration, and this short-term warming may push the climate system into feedback loops that accelerate warming.…”
Section: Bioenergymentioning
confidence: 99%
“…The payback time for the carbon debt was reported to range from 44 to 104 years, depending on forest type and growth. Following the work by Sterman, Siegeland Rooney-Varga [ 48 ], Rolls and Forster [ 51 ] replicated the model and modified the input parameters to predict the forest carbon uptake and payback time of the carbon debt with considering the uncertainty in forest growth. This study showed the payback time largely dependent on the uncertainty of forest growth curves [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following the work by Sterman, Siegeland Rooney-Varga [ 48 ], Rolls and Forster [ 51 ] replicated the model and modified the input parameters to predict the forest carbon uptake and payback time of the carbon debt with considering the uncertainty in forest growth. This study showed the payback time largely dependent on the uncertainty of forest growth curves [ 51 ]. Jonker, Junginger and Faaij [ 49 ] calculated the carbon payback period for wood pellets from softwood forest, taking into consideration the temporal profiles of forest growth under several management scenarios.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation